Current trends in research on innovation in social sciences: a bibliometric study - Alemán Ramos, Pedro Francisco; Morales Almeida, Paula (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
Innovation has always been felt as a concern for all societies, which is why it has been and is an integral part of humanity. This study focuses on describing the con-temporary scientific production on innovation in the social sciences and analyzing the lines of research in this field. For this, bibliometry was used as a quantitative method. Scientific production shows a growing trend, as of 2016, with an annual growth rate in the period 2010-2021 of 11.5%. Four topics of interest were iden-tified: innovation and technology; tourism; ethics and governance and social and communication.